Implementation auditory-intellectually-repetition of redox material to improve learning outcomes in class X high school students 1 Krueng Barona Jaya - Abdul Gani; Maya Paramitha Mirda; Ade Ismayani (Pascasarjana Universitas Negeri Medan, 2020)
Students have different levels of knowledge that can affect learning outcomes. The implementation of learning models in the classroom can also affect student learning outcomes. This study aims to determine how the effect of the implementation of the Auditory Intellectually Repetition (AIR) learning model on redox material in class X SMAN 1 Krueng Barona Jaya. This type of research is descriptive and the approach used is a qualitative approach. This study focuses on several aspects, namely learning outcomes, activities, and students' responses. The subjects in this study were students in class X-MIA1 SMAN 1 Krueng Barona Jaya. Data collection tools used were student activity observation sheets, evaluation questions, and student response questionnaires. Data were collected using these three tools and then the percentage of the results was seen. The results of the analysis of students' learning completeness were obtained that 80% of students had completed and 20% of students did not complete. The results of observations of students 'activities were seen to have developed from the first meeting, namely 92.11% to 93.75% at the second meeting, while the results of the students' responses were obtained an average percentage of 85.56%. This shows that the implementation of the AIR learning model received a positive response from students and can be used as an effective model to use in redox material.Keywords: Auditory intellectually repetition, Learning outcomes, Student activities